Tuning the Photonic Behavior of Symmetrical bis-BODIPY Architectures: The Key Role of the Spacer Moiety - Oliden-Sánchez, Ainhoa; Sola-Llano, Rebeca; Bañuelos, Jorge; García-Moreno, Inmaculada; Uriel, Clara; López, J. Cristobal; Gómez, Ana M. (Frontiers in Chemistry, 2019)
Herein we describe the synthesis, computationally assisted spectroscopy and lasing properties of a new library of symmetric bridged bis-BODIPYs differing in the nature of the spacer. Thus, access to a series of BODIPY dimers is straightforward through synthetic modifications of the pending ortho-hydroxymethyl group of readily available C-8 (meso) ortho-hydroxymethyl phenyl BODIPYs. In this way, we have carried out the first systematic study of the photonic behavior of symmetric bridged bis-BODIPYs effectively modulated by the length and/or steroelectronic properties of the spacer unit. The designed bis-BODIPYs display bright fluorescence and laser emission in non-polar media. The fluorescence response is ruled by the induction of a non-emissive intramolecular charge transfer (ICT) process, which enhances significantly in polar media. The effectiveness of the fluorescence quenching as well as the prevailing charge transfer mechanism (from the spacer itself or between the BODIPY units) rely directly on the electron-releasing ability of the spacer. Moreover, the linker moiety can also promote intramolecular excitonic interactions leading to excimer-like emission characterized by new spectral bands and the lengthening of lifetimes. The substantial influence of the bridge moiety on the emission behavior of these BODIPY dyads as well as their solvent-sensitivity pinpoint the intricate molecular dynamics upon excitation in multichromophoric systems. In this regard, the present work represents a breakthrough in the complex relationship between the molecular structure of the chromophores and their photophysical signatures, thus providing key guidelines to rationalize the design of tailored bis-BODIPYs with potential advanced applications.